1994
DOI: 10.1111/j.1476-5381.1994.tb13102.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding and functional properties of hexocyclium and sila‐hexocyclium derivatives to muscarinic receptor subtypes

Abstract: 1 We have compared the binding properties of several hexocyclium and sila-hexocyclium derivatives to muscarinic M, receptors (in rat brain, human neuroblastoma (NB-OK 1) cells and calf superior cervical ganglia), rat heart M2 receptors, rat pancreas M3 receptors and M4 receptors in rat striatum, with their functional antimuscarinic properties in rabbit vas deferens (MI/M4-like), guinea-pig atria (M2), and guinea-pig ileum (M3) muscarinic receptors.2 Sila-substitution (C/Si exchange) of hexocyclium (-* sila-hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Tissues were isolated from adult guinea pigs of either sex or from male New Zealand White rabbits previously killed by cervical dislocation or intravenous injection of 120 mg/kg pentobarbitone sodium, respectively. The methods used have been described in detail previously (Waelbroeck et al, 1994(Waelbroeck et al, , 1996.…”
Section: Experiments In Isolated Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues were isolated from adult guinea pigs of either sex or from male New Zealand White rabbits previously killed by cervical dislocation or intravenous injection of 120 mg/kg pentobarbitone sodium, respectively. The methods used have been described in detail previously (Waelbroeck et al, 1994(Waelbroeck et al, , 1996.…”
Section: Experiments In Isolated Organsmentioning
confidence: 99%
“…W84 was synthesized by Dr. Joachim Pfeffer (University of Kiel, Germany) according to Wassermann (1970). APE and 4-Cl-McN-A-343 were synthesized by Dr. Ulrich Moser (University of Frankfurt, Germany) according to Waelbroeck et al (1994).…”
Section: Drugsmentioning
confidence: 99%
“…Quantitation is done other has serious adverse drug reactions [8]. It was by ESI-MS in the selected ion monitoring (SIM) indicated by previously published studies [7,[9][10][11][12][13][14][15] mode. The entire analysis can be automated and that (R)-enantiomers of THP and procyclidine have requires little operator skill.…”
Section: Introductionmentioning
confidence: 99%
“…subtypes whereas (2)-enantiomer was nearly devoid of such selectivity [16]. However, these studies showed no conclusions about the potency of the ''high affinity'' enantiomer because no correlation Experimental was observed between its potency and the affinity ratios of the two enantiomers [7,10]. This situation Materials was in part due to the lack of sensitive stereoselective analytical methodology for the determination of DL-Trihexyphenidyl hydrochloride, DL-procycthese enantiomers in biological fluids.…”
Section: Introductionmentioning
confidence: 99%